Sagot :
Answer: RHS = 1/(10 - 6) = 1/4
LHS = RHS = 1/4
Given : (x - 6 )/ (x² - 4x - 12) + 2/(x + 2) = 1/(x - 6)
To Find : Solve for x and verify
Solution:
(x - 6 )/ (x² - 4x - 12) + 2/(x + 2) = 1/(x - 6)
x² - 4x - 12 = (x - 6)(x + 2)
=(x - 6 )/ (x - 6)(x + 2) + 2/(x + 2) = 1/(x - 6)
Hence Denominator LCD = (x - 6)(x + 2) = x² - 4x - 12
Multiply both sides of the equation by its the LCD. (x - 6)(x + 2)
= (x - 6) + 2(x - 6) = x + 2
=> x - 6 + 2x - 12 = x + 2
=> 3x - 18 = x + 2
=> 2x = 20
=> x = 10
(x - 6 )/ (x² - 4x - 12) + 2/(x + 2) = 1/(x - 6)
Substitute x = 10
LHS = (10 - 6 )/ (10² - 4(10) - 12) + 2/(10 + 2)
= 4/(100 - 40 - 12) + 2/12
= 4/48 + 2/12
= 1/12 + 2/12
= 3/12
= 1/4
RHS = 1/(10 - 6) = 1/4
LHS = RHS = 1/4
Learn More:
Simplify 14÷(3 of 2-3+4) -9 (5-3)
brainly.in/question/3715630
solve the linear equation x+1/2x+3=3/8 - Brainly.in
brainly.in/question/1418370